The former pleasure house of Prince Galitzin in the Prater - Prixner, Gottfried, 1746-1819 (engraver):::Creator::::::::::::; Weidmann, F.C. (Franz Carl), 1787-1867 (author):::Contributor:::::::::::: (Vienna; Austria; R. Sammer, Buchhändler beyn Kärntherthore, 2020)
Original copper engraving of the former Galitzin Lusthaus in the Prater in Vienna, with one page of explanatory text.